PENGARUH KOMITMEN TERHADAP KEPUASAN KERJA KARYAWAN PT. TOYOPLAS MANUFACTURING INDONESIA DI CIKARANG PUSAT - Laelatul Zulfa; Maulkre Her Susilo (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2022)
Work commitment is a condition of an employee who favors a particular organization, as well as its goals and desires to maintain membership in the organization (Robbins and Judge, 2008). The impact of a commitment is also very strong, if in an organization where employees do not have a strong commitment or agreement at work, then the goals to be addressed by the organization will mostly fail or will not succeed.“In this study there are two variables, namely the independent variable X (Commitment) and the dependent variable Y (Job Satisfaction) which aims to determine a commitment to employee job satisfaction at PT. Toyoplast Manufacturing Indonesia in Central Cikarang.“The method used in this study in two ways, namely descriptive analysis method used to discuss the problem formulation of how employee commitment and employee job satisfaction at PT. Toyoplast Manufacturing Indonesia in Central Cikarang, then the analytical verification method used to discuss the problem formulation how much influence a commitment to employee job satisfaction at PT. Toyoplast Manufacturing Indonesia in Central Cikarang. In this study, it is necessary to have a sample that is considered representative with a population of 150 in which 20% are taken 30 samples. The data used is primary data collected through observation, interviews, and questionnaires (questionnaire) while secondary data obtained from the literature and the value of constants as a comparison of research. To measure the magnitude of the effect of these variables, Simple Linear Regression, CorrelationCoefficient and Coefficient of Determination were used with the help of the IBM SPSS application program. The results showed that from Simple Linear Regression, the Coefficient of Determination (KD) value was 39.60% with a Correlation Coefficient value of 0.630, so that it has the understanding that commitment greatly influences employee job satisfaction at PT. Toyoplast Manufacturing Indonesia in Central Cikarang but not the only factor, where there are still 60.40% another influential variable.Keywords: Commitment and Job Satisfaction